2020
DOI: 10.1186/s12885-020-07621-7
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram-derived prediction of pathologic complete response (pCR) in breast cancer patients treated with neoadjuvant chemotherapy (NCT)

Abstract: Background Previous research results on the predictive factors of neoadjuvant chemotherapy (NCT) efficacy in breast cancer are inconsistent, suggesting that the ability of a single factor to predict efficacy is insufficient. Combining multiple potential efficacy-related factors to build a model may improve the accuracy of prediction. This study intends to explore the clinical and biological factors in breast cancer patients receiving NCT and to establish a nomogram that can predict the pathologic complete resp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 45 publications
2
11
1
Order By: Relevance
“…The CTNeoBC pooled analysis included 11955 patients suggested that the frequency of pCR in patients with clinical-nodal-positive and hormone-receptorpositive tumors was low (44). Ki67 expression was related to tumor cell proliferation, several studies revealed that patients with higher Ki67 expression were more likely to achieve pCR (45)(46)(47).Most of the above indicators are consistent with the existing literature. However, there was no significant correlation between HER2 status and pCR, which is inconsistent with previous studies (4).…”
Section: Discussionsupporting
confidence: 79%
“…The CTNeoBC pooled analysis included 11955 patients suggested that the frequency of pCR in patients with clinical-nodal-positive and hormone-receptorpositive tumors was low (44). Ki67 expression was related to tumor cell proliferation, several studies revealed that patients with higher Ki67 expression were more likely to achieve pCR (45)(46)(47).Most of the above indicators are consistent with the existing literature. However, there was no significant correlation between HER2 status and pCR, which is inconsistent with previous studies (4).…”
Section: Discussionsupporting
confidence: 79%
“…It has been shown that molecular biomarkers are correlated with NAC sensitivity in breast cancer ( 27 ). For example, HR negativity and HER2 positivity were associated with higher pCR rates [odds ratio (OR) = 0.497 and 1.833, respectively] ( 28 ). The IHC4 score combining ER, PR, HER2, and Ki67 expression levels was associated with pCR rate; furthermore, the lower the IHC4 score, the higher the pCR rate in the ER-positive breast cancer patients (AUROC = 0.613) ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reliable markers of chemosensitivity help select patients who most benefit from NACT[ 19 ]. Previous studies on the candidate predictors of NACT efficacy in breast cancer patients are discordant, suggesting that the potential predictors to predict efficacy is insufficient[ 20 - 23 ].…”
Section: Discussionmentioning
confidence: 99%